The Plant Genome special section: Grain quality and nutritional genomics for breeding next‐generation crops - Pandey, Manish K.; Mir, Reyazul Rouf; Sreenivasulu, Nese (Wiley, 2023)
By 2050, the world's population is expected to reach 9.8 billion according to United Nations predictions (https://www.un.org/en/desa/world-population-projected-reach-98-billion-2050-and-112-billion-2100). As a result, crop yields must roughly double in order to feed an expanding global population while still satisfying consumer demands for grain quality and nutrition. In addition to enhancing the nutritional value of food crops, making available affordable, nutrient-dense food, especially to those who are economically disadvantaged, will be a central pillar to address food and nutritional security. The strategy for improving grain quality and nutritional traits in breeding programs has been prioritized with the recent advancements in phenotyping of seeds and grains (metabolomics, mineral and vitamins, assessing the quality of starch, proteins and lipids, and capturing consumer preferred traits), sequencing technologies to do high-throughput genotyping, functional genomics aided gene discovery, high-resolution trait mapping and superior haplotype discovery, as well deploying genomic selection tools in a variety of crops (Pandey et al., 2016; Varshney et al., 2019). To improve population dietary patterns, a new generation of foods and ingredients with improved intrinsic nutritional quality and preferred grain quality attributes needs to be generated through advanced breeding methods. This will help to improve public health by increasing nutritional density and optimizing the quality of complex carbohydrates, proteins, and lipids. By utilizing and integrating both modern and traditional breeding techniques, it is possible to hasten the production of new crop types with improved yield, grain, and nutritional quality. This special issue highlights the most significant findings, which cover developments in high-throughput genomics, including genomic prediction of traits related to grain quality, and enhancement of nutritive traits in cereals (rice, wheat, maize, and oat) as well as legume crops like groundnut. Overall, this special issue includes a collection of studies deciphering genetic mechanisms of micronutrients covering minerals such as grain iron (Fe), zinc (Zn), and vitamin enrichment (tocochromanols), pigmented bioactives, amino acids, dietary fiber, fatty acid composition, food safety, and end user grain quality traits in cereals and selected legumes.